High-density VERPs show distinct mechanisms for global form and motion processing in adults and infants - Braddick, O; Wattam-Bell, J; Birtles, D; Atkinson, J; von Hofsten, C; Nyström, P (Association for Research in Vision and Ophthalmology, 2007)
Sensitivity to global form and global motion are presumed indicators of extra-striate processing in ventral- and dorsal-stream visual areas respectively. Previously we have studied development in the two streams using single-channel steady-state visual evoked potentials (VEPs). We have extended this approach to high-density (128-channel) VERP recordings, to examine whether global form and motion responses have distinguishable topographic signatures. In the form stimulus, dots form short concentric arcs giving a static global circular organization. For global motion the dots moved along similar arcs, yielding global rotation. Each of these patterns alternated (2 Hz) with patterns of randomly arranged arcs with no global structure. A positive VERP response to global organization is indicated by a first harmonic (F1) frequency component with significantly higher amplitude than the background noise. Adult subjects showed strong, posteriorly-located F1 responses to both form and motion. The focus of the motion response was close to the midline, while the form response was more lateralised. A MANOVA on F1 amplitudes at each EEG channel confirmed this topographic difference as a significant form/motion x channel interaction. In initial tests on 3-5 month old infants, the majority showed significant global motion responses close to the occipital midline, but fewer showed a significant form response, consistent with our previous findings that global form processing lags behind motion in development. Where there were responses to both stimuli there was, as in adults, a significant difference in topography with form responses having a more lateralised focus. Results on a wider range of infants will be reported. These results show that global form and motion responses have distinct scalp distributions, implying distinct neural sources, in both adults and infants. The high-density multichannel method opens the possibility of tracking developmental changes, and the effects of perinatal risk factors, in the relationship between these sources.